2016
DOI: 10.1159/000450617
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Plausibility of 5-Alpha-Reductase Inhibitor Syndrome

Abstract: Postfinasteride syndrome (PFS) is a term recently coined to characterize a constellation of reported undesirable side effects described in postmarketing reports and small uncontrolled studies that developed during or after stopping finasteride treatment, and persisted after drug discontinuation. Symptoms included decreased libido, erectile dysfunction, sexual anhedonia, decreased sperm count, gynecomastia, skin changes, cognitive impairment, fatigue, anxiety, depression, and suicidal ideation. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 45 publications
(85 reference statements)
0
32
0
Order By: Relevance
“…It is possible that patients may still be opting for surgery despite wide availability of BPH drugs due to concerns regarding their potential for undesirable side-effects. 5ARIs and ABs have previously been associated with long-term ejaculatory and erectile dysfunctions, which also formed the basis of a class action law suit against finasteride manufacturer Merck in 2016 [3,36]. Future trends may be influenced by alternative treatments, such as prostate artery embolisation (PAE) as an emerging minimally invasive alternative to long-term medical therapy, with previous studies demonstrating its feasibility and short-term efficacy, especially in poor surgical candidates [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that patients may still be opting for surgery despite wide availability of BPH drugs due to concerns regarding their potential for undesirable side-effects. 5ARIs and ABs have previously been associated with long-term ejaculatory and erectile dysfunctions, which also formed the basis of a class action law suit against finasteride manufacturer Merck in 2016 [3,36]. Future trends may be influenced by alternative treatments, such as prostate artery embolisation (PAE) as an emerging minimally invasive alternative to long-term medical therapy, with previous studies demonstrating its feasibility and short-term efficacy, especially in poor surgical candidates [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review and a meta‐analysis of 6460 patients conclude that dutasteride is effective for improving BPH, however, use in this patient population corresponds with an increased risk of sexual dysfunction . When prescribed off‐label for AGA in an otherwise healthy population, a literature review of adverse side‐effects associated with 5αRIs concluded that persistent sexual side‐effects were only documented in low‐quality studies with strong bias selection as participants were part of an Internet blog . High‐quality studies were found to report persistent sexual side‐effects more frequently in placebo groups versus treated individuals suggesting that sexual dysfunction is not a direct result of therapy .…”
Section: Introductionmentioning
confidence: 99%
“…7 High-quality studies were found to report persistent sexual side-effects more frequently in placebo groups versus treated individuals suggesting that sexual dysfunction is not a direct result of therapy. 7 A literature review of studies prescribing 5aRIs for androgenetic AGA versus BPH revealed a significant association between sexual dysfunction adverse events in BPH patients but not among AGA patients. 8 Some suggest age may be a confounding factor, as sexual dysfunction increases with age, and BPH generally affects older men and necessitates a higher dose of 5aRI.…”
Section: Introductionmentioning
confidence: 99%
“…A second 5α-reductase inhibitor, dutasteride, was approved in 2001 for benign prostatic hyperplasia. Emerging post-marketing reports of persistent depression and sexual side effects have led to growing concerns about the safety of 5α-reductase inhibitors and prompted product labelling changes in many regulatory jurisdictions 1234. Since 2008, at least 17 countries including the United Kingdom and the United States have warned prescribers of the potential for depression, sexual side effects, or both with finasteride 5…”
mentioning
confidence: 99%
“…Post-finasteride syndrome is an ill defined and controversial syndrome associated with a constellation of sexual, physical, and psychological symptoms that develop during or after finasteride exposure and persist after discontinuation (box 1). 35 The incidence of post-finasteride syndrome is unknown, as are the biological mechanisms, but we know that 5α-reductase inhibitors reduce synthesis of brain neurosteroids, which affect mood, cognition, and libido 36…”
mentioning
confidence: 99%